High-Grade Sarcoma Arising in the Background of Growing Teratoma Syndrome; A Rare Case. (28th October 2021) - Sadiq, Q; Mohammed, S; Yadak, N; Khan, F
Abstract: Introduction/Objective: Growing teratoma syndrome is a rare condition seen in patients with a history of immature teratomas or mixed germ cell tumor status post-treatment. It usually occurs within the first two years of diagnosis but rarely can be seen years later. Methods/Case Report: We report a case of a 48-year-old female with a previous history of ovarian malignancy in adolescence status post-TAH/BSO and chemotherapy, now presenting with a 23 cm multi cystic septate mass with some solid components in the subdiaphragmatic area, extending into the liver on imaging. Nodular implants along the surface of the right hepatic lobe and multiple peritoneal implants were seen. Histology of peritoneal implants showed fibro adipose tissue admixed with rare scattered glandular elements, epithelial fragments, and mature neuroglial tissue, consistent with mature teratoma. Liver biopsy revealed short fascicles of spindled, epithelioid and rhabdoid tumor cells admixed with foci of the myxoid stroma. Scattered moderate cytologic atypia, atypical mitosis, and necrosis were appreciated. Tumor cells showed strong and diffuse reactivity to vimentin while being negative for epithelial, neural/mesenchymal, mesothelial, sex cord-stromal, and germ cell differentiation markers. Differential diagnostic considerations included spindle cell transformation of a germ cell tumor or high-grade sarcoma, not otherwise specified arising in the background of growing teratoma syndrome. FISH testing for isochromosome 12p was negative excluding sarcomatoid germ cell tumor. Results (if a Case Study enter NA): NA Conclusion: This case study highlights the importance of considering the rare complication of high-grade sarcoma arising in the background of growing teratoma syndrome.